Pengaruh Atmosfer Café, Kualitas Produk dan Gaya Hidup terhadap Kepuasan Pelanggan (Studi pada Dokter Kupi Café di Kota Lhokseumawe) - Adnan Adnan (Jurnal Visioner & Strategis, 2020)
This study aims to determine and analyze the effect of cafe atmosphere, product quality and lifestyle on consumer satisfaction at Doctor Kupi Café in Lhokseumawe City. The research sample was taken as many as 100 respondents from the Kupi Café Doctor Customer, through the distribution of questionnaires using the Purposive Sampling method, which is a sampling technique with certain considerations that is only given to customers. The results showed that there are partially three independent variables namely café atmosphere, product quality and lifestyle that have a significant influence on customer satisfaction. While simultaneously through the café atmosphere F test, product quality and lifestyle simultaneously influence customer satisfaction. Adjusted R square of 0.729 shows that 72.9 % of customer satisfaction variables are influenced by the three independent variables used in the regression equation. While the remaining 27.1 % is influenced by variables not included in this study.  Keywords:  Café Atmosphere, Product Quality, Lifestyle, Customer Satisfaction